A Russian Rhetoric of Form in the Music of Witold Lutosławski - Douglas Rust (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
The capacity to write music that clearly conveys one formal meaning in its immediate context, and yet expresses a different meaning in a wider context, is one of the most interesting attributes in the musical style of Witold Lutosławski (1913–94), who cultivated multiple temporalities in his compositions using the musical language of twentieth-century modernism. In developing these innovations, he was inspired by his Russian-trained composition teacher to use metaphors of rhetoric and drama to model the “psychology” of his musical forms on the example of Beethoven’s sonatas. This article will suggest ways in which Lutosławski’s manner of composing music in multiple temporalities can be understood as a creative response to the musical training he received at the Warsaw Conservatory. Also, it will explore the significance of the composer’s claim that the analytical methods he learned were descended from Russian traditions. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part II).